2001
DOI: 10.1016/s1010-7940(01)00700-x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the intraoperative transit time measurements of coronary bypass flow

Abstract: The bypass flow was affected by such a large number of factors that only measuring the bypass flow rate could not sufficiently predict either stenosed or narrowed grafts. However, ITA grafts bypassed to the coronary arteries with less stenosis were shown to more easily become narrowed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 11 publications
2
33
0
1
Order By: Relevance
“…This could explain that measured blood flow in SVG is significantly lower in the (1G) case than in the (3G) case (Table 2). In other words, as demonstrated by Hirotani et al 10 and Glineur et al, 9 the status of the distal supplied territory influences the flow in the graft.…”
Section: Case (1g): Right Graft Working; No Left Graftsmentioning
confidence: 92%
“…This could explain that measured blood flow in SVG is significantly lower in the (1G) case than in the (3G) case (Table 2). In other words, as demonstrated by Hirotani et al 10 and Glineur et al, 9 the status of the distal supplied territory influences the flow in the graft.…”
Section: Case (1g): Right Graft Working; No Left Graftsmentioning
confidence: 92%
“…The main commercial systems available for this purpose are ultrasonic and electromagnetic devices. The electromagnetic flowmeter is efficient in detecting graft stenosis; however, it is sensitive to the patient hematocrit rate, especially in smaller vessels, such as the internal thoracic artery (Canver et al, 1997;Hirotani et al, 2001;Tabrizchi and Pugsley, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Flow pattern is predominantly diastolic in all grafts but is more marked in the left coronary system; because of a smaller right ventricular transmyocardial pressure gradient, there is a comparatively greater systolic flow component in grafts to the right coronary system [2]. A number of studies have reported the usefulness and efficacy of TTFM [10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Takami et al [12,13] described the usefulness of TTFM in the detection of intraoperative graft failure of several types of grafts.…”
Section: Ultrasound Technologymentioning
confidence: 99%